Landfill leachates as a source of pathogenic environmental impact - Ivanenko, Dmitrо (National Technical University "Kharkiv Polytechnic Institute", 2024)
Domestic waste management in Ukraine has reached a critical level, as the vast majority of the total amount of waste generated is stored in open areas. Solid household waste is deposited in landfills and landfills with a total area of about 9 thousand hectares. Not counting the countless amounts of waste generated as a result of combat maidens, 37.6 billion tonnes of waste have been accumulated in our country, of which 1.6 billion tonnes are hazardous. This situation leads to significant man-made pressure on the environment and the emergence of an environmental disaster in general. In this context, it is important to develop effective mechanisms for environmentally safe collection, transportation and disposal of household waste, as well as to improve the efficiency of existing waste management approaches.
Keywords: municipal solid waste; landfills; water systems; pollution; pathogens; natural environment